Preliminary Investigation on the Energy Harvesting of Vortex-Induced Vibration with the Use of Magnet - Adnan, Nur Fatimah; Lee, Kee Quen; Kang, Hooi Siang; Wong, Keng Yinn; Tan, Hui Yi (Progress in Energy and Environment, 2022)
The utilization of natural resources as renewable energy is thriving as its innovation brings clean energy, environmentally friendly and also cut down costs. Hence, the purpose of this study is to propose a technique to enhance the output voltage of piezoelectric as an energy harvesting device by applying nonlinear magnetic forces from a phenomenon called vortex induced vibration (VIV). This harvester device is designed with a presence of two magnets that placed at the bottom of a circular cylinder and on the lower base. The mechanical conversion energy that is studied is the vibration from circular cylinder’s oscillation through a phenomenon called Vortex Induced Vibration by using piezoelectric transducer. A VIV-based energy harvester has been fabricated and carried out in water flow to observe the optimum output voltage that can be generated. Three different lengths of piezoelectric cantilever plates and two magnet distances are tested to investigate the influence of system’s stiffness and the repulsive force to the harvested energy. From the experiment, it is observed that a lower stiffness of the system provides higher harvested voltage. In addition, the presence of magnets shows a greater output voltage due to the action of nonlinear magnetic forces where the position between two magnets able to shift the synchronization region thus, showing a greatly wider synchronization region and increasing the performance of VIV-based energy harvesting system.